Self-adhesive polymer modified asphalt waterproof coiled material thermal aging resistant asphalt and application thereof
By blending high-temperature coal asphalt with medium-temperature coal asphalt, a self-adhesive polymer modified asphalt waterproof roll with a softening point of 95 to 110°C is obtained, which solves the precipitation problem caused by poor compatibility between high-temperature coal asphalt and petroleum asphalt, and improves the heat-proof aging and self-adhesiveness of the waterproof roll.
Patent Information
- Application Number
- CN202510101107.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-25
AI Technical Summary
The precipitation problems caused by poor compatibility between high-temperature coal asphalt and petroleum asphalt, as well as the problem that their softening points affect self-adhesion.
High-temperature coal asphalt and medium-temperature coal asphalt were blended to obtain a self-adhesive polymer modified asphalt waterproof roll with a softening point of 95 to 110°C, and added to the waterproof roll with styrene butadiene rubber as the modifier.
It effectively improves the heat-proof aging properties of the waterproof coil, avoids precipitation caused by poor compatibility between high-temperature coal asphalt and petroleum asphalt, and maintains self-adhesion.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building waterproof materials, and in particular relates to a self-adhesive polymer modified asphalt waterproofing coiled material anti-heat aging asphalt and application thereof. Background Art
[0002] High-temperature coal tar contains more aromatic components, especially phenols, which can prevent thermal aging of rubber materials. However, high-temperature coal tar has a high softening point. Adding it to self-adhesive asphalt rolls will affect the self-adhesiveness of the rolls, and the softening point needs to be lowered to below 110°C. In addition, high-temperature coal tar has poor solubility in petroleum asphalt and modified asphalt, and is prone to precipitation. The processing of waterproof rolls requires treatment to eliminate precipitation and improve solubility. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt and its application. When the asphalt is used in the waterproof membrane, it will not produce precipitation caused by the poor compatibility between high-temperature coal tar and petroleum asphalt, and effectively improve its heat aging resistance.
[0004] The present invention provides a polymer-modified asphalt waterproofing roll material heat-resistant asphalt, which is prepared by the following method:
[0005] The high-temperature coal tar and the medium-temperature coal tar are blended to obtain the heat-resistant aging asphalt for the self-adhesive polymer modified asphalt waterproofing membrane;
[0006] The high-temperature coal tar has a softening point of ≥130°C and an ash content of ≤15%; the medium-temperature coal tar has a softening point of 70-85°C and an ash content of ≤10%; and the anti-heat-aging asphalt has a softening point of 95-110°C.
[0007] Preferably, the mass ratio of the high-temperature coal tar pitch to the medium-temperature coal tar pitch is (1:2) to (1:6).
[0008] Preferably, the blending temperature is 230-260°C and the blending time is 30-35 minutes;
[0009] The blending is carried out under stirring conditions, and the stirring rate is 300-400 rpm.
[0010] Preferably, the ash content of the heat-aging resistant asphalt in the self-adhesive polymer modified asphalt waterproofing membrane is ≤15wt%.
[0011] The present invention provides a self-adhesive polymer modified asphalt waterproofing coiled material, and the raw materials for preparing the self-adhesive polymer modified asphalt waterproofing coiled material include the anti-heat aging asphalt described in the above technical solution.
[0012] Preferably, the self-adhesive polymer modified asphalt waterproofing membrane uses styrene-butadiene rubber as a modifier.
[0013] Preferably, the following raw materials are included by mass fraction:
[0014] 70# asphalt 17-25%; 200# asphalt 27-35%; styrene-butadiene rubber powder 2.8-4%; thermoplastic styrene-butadiene rubber 1.5-2.5%; L-series modified petroleum resin 1-1.5%; 75-85 mesh waste tire rubber powder 15-20%; mineral powder 25-30% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 2-5%.
[0015] The invention provides a self-adhesive polymer modified asphalt waterproofing coiled material heat-aging-resistant asphalt, which is prepared by the following method: high-temperature coal tar and medium-temperature coal tar are blended to obtain the self-adhesive polymer modified asphalt waterproofing coiled material heat-aging-resistant asphalt; the high-temperature coal tar has a softening point of ≥130°C and an ash content of ≤15%; the medium-temperature coal tar has a softening point of 70-85°C and an ash content of ≤10%; the heat-aging-resistant asphalt has a softening point of 95-110°C. The asphalt is blended with high-temperature coal tar and medium-temperature coal tar to obtain a blended asphalt with a softening point of 95-110°C, which is added to a waterproofing coiled material with styrene-butadiene rubber as a modifier, and the heat-aging resistance of the self-adhesive asphalt coiled material can be improved, and precipitation caused by the poor compatibility between high-temperature coal tar and petroleum asphalt will not be generated. DETAILED DESCRIPTION
[0016] The present invention provides a self-adhesive polymer modified asphalt waterproofing roll material heat-resistant asphalt, which is prepared by the following method:
[0017] The high-temperature coal tar and the medium-temperature coal tar are blended to obtain the heat-resistant aging asphalt for the self-adhesive polymer modified asphalt waterproofing membrane;
[0018] The softening point of the high-temperature coal tar pitch is ≥130°C, and the ash content is ≤15wt%; the softening point of the medium-temperature coal tar pitch is 70-85°C, and the ash content is ≤10%; the softening point of the anti-heat aging asphalt is 95-110°C.
[0019] The high-temperature coal tar pitch used in the present invention has a softening point of ≥130°C and an ash content of ≤15wt%; in a specific embodiment, the high-temperature coal tar pitch has a softening point of 150°C and an ash content of 10%.
[0020] The medium-temperature coal tar pitch used in the present invention has a softening point of 70-85°C and an ash content of ≤10wt%. In a specific embodiment, the medium-temperature coal tar pitch has a softening point of 80°C and an ash content of 8wt%.
[0021] The present invention blends high-temperature coal tar and medium-temperature coal tar; the blending temperature is 230-260° C. and the time is 30-35 minutes;
[0022] The blending is carried out under stirring conditions, and the stirring rate is 300-400 rpm.
[0023] The heat-aging-resistant asphalt for the self-adhesive polymer-modified asphalt waterproofing coil obtained by the present invention is also called blended asphalt, and has a softening point of 95-110° C. and an ash content of ≤15%.
[0024] The present invention applies the above-mentioned self-adhesive polymer modified asphalt waterproofing membrane heat-resistant asphalt to waterproofing membranes, specifically to self-adhesive polymer modified asphalt waterproofing membranes with styrene-butadiene rubber as a modifier, which can improve the heat-resistant aging property of the self-adhesive asphalt membranes.
[0025] The present invention provides a self-adhesive polymer modified asphalt waterproofing coiled material, and the raw materials for preparing the self-adhesive polymer modified asphalt waterproofing coiled material include the anti-heat aging asphalt described in the above technical solution.
[0026] The self-adhesive polymer modified asphalt waterproofing coiled material of the present invention uses styrene-butadiene rubber as a modifier.
[0027] The self-adhesive polymer modified asphalt waterproofing membrane provided by the present invention comprises the following raw materials by mass fraction:
[0028] 70# asphalt 17-25%; 200# asphalt 27-35%; styrene-butadiene rubber powder 2.8-4%; thermoplastic styrene-butadiene rubber 1.5-2.5%; L-series modified petroleum resin 1-1.5%; 75-85 mesh waste tire rubber powder 15-20%; mineral powder 25-30% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 2-5%.
[0029] The thermoplastic styrene-butadiene rubber in the present invention is SBS791. The mineral powder in the present invention is natural stone processing powder; it can be one or more of light calcium, heavy calcium, talcum powder and calcium carbonate.
[0030] The waterproof coiled material prepared by the above formula of the present invention has excellent heat aging resistance.
[0031] In the present invention, the self-adhesive polymer modified asphalt waterproofing membrane comprises the following raw materials by mass fraction:
[0032] 70# asphalt 21.5%; 200# asphalt 27.5%; styrene-butadiene rubber powder 3.5%; thermoplastic styrene-butadiene rubber 2%; L-series modified petroleum resin 1%; 80-mesh waste tire rubber powder 16.5%; talcum powder 26% and self-adhesive polymer modified asphalt waterproofing membrane anti-heat aging asphalt 2%;
[0033] Or 70# asphalt 19.5%; 200# asphalt 29%; styrene-butadiene rubber powder 2.9%; thermoplastic styrene-butadiene rubber 1.6%; L-series modified petroleum resin 1.5%; 80-mesh waste tire rubber powder 15.5%; talcum powder 27% and self-adhesive polymer modified asphalt waterproofing membrane anti-heat aging asphalt 3%;
[0034] Or 70# asphalt 17%; 200# asphalt 29%; styrene-butadiene rubber powder 3%; thermoplastic styrene-butadiene rubber 1.5%; L series modified petroleum resin 1%; 80-mesh waste tire rubber powder 18%; talcum powder 27% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 3.5%.
[0035] The processing temperature of the waterproof coiled material prepared from the above raw materials in the present invention is 175-195° C., wherein the shearing and swelling time of styrene butadiene rubber powder and thermoplastic styrene butadiene rubber is 1.5 hours, and the swelling time of waste tire rubber powder is 1 hour.
[0036] The present invention preferably mixes 17-25% of 70# asphalt, 27-35% of 200# asphalt, 2.8-4% of styrene-butadiene rubber powder, 1.5-2.5% of thermoplastic styrene-butadiene rubber, 1-1.5% of L-series modified petroleum resin, 25-30% of mineral powder and 2-5% of self-adhesive polymer modified asphalt waterproofing membrane anti-heat aging asphalt, and finally adds 15-20% of 75-85 mesh waste tire rubber powder; after adding the waste tire rubber powder, stir evenly for 25-35 minutes to complete. The shear speed used in the preparation of the waterproofing membrane is 3000-4000rpm, and the stirring speed is 300-400rpm.
[0037] The present invention adopts the peel strength test method described in GB 23441-2009:
[0038] A 1.5mm thick single-sided self-adhesive waterproof membrane was used as a test piece. The lower surface of one test piece was bonded to the upper surface of another test piece. The bonding surface was 50mm×75mm. A roller with a mass of 2kg and a width of (50-60)mm was used to roll the test piece three times. After bonding, the test piece was left for 24 hours. The peel strength was calculated using the maximum force in N / mm. The arithmetic mean of the results of the five test pieces was taken as the test result.
[0039] Low temperature flexibility test method:
[0040] The test is conducted in accordance with GB / T328.14-2007. A 1.5mm thick single-sided self-adhesive waterproof membrane is used as the test piece, and the bending axis diameter is 20mm. Ten test pieces are taken longitudinally, and five test pieces are tested on the upper surface and five test pieces on the lower surface. If at least four of the five test pieces on each side are visually free of cracks, the side passes. If both the upper and lower sides pass, it is considered to meet the low-temperature flexibility requirements.
[0041] Treatment methods for thermal aging:
[0042] Take a 1.5mm thick single-sided self-adhesive waterproof membrane as the test piece. Place the test piece horizontally in a (70±2)℃ oven for 7d±2h, take it out and place it at (23±2)℃ for 24h to cut the test piece.
[0043] In order to further illustrate the present invention, a self-adhesive polymer modified asphalt waterproofing roll material anti-heat aging asphalt and its application provided by the present invention are described in detail below in combination with embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0044] The high temperature coal tar pitch used in the following examples of the present invention is Ningxia Xinhuawei high temperature coal tar pitch, with a softening point of 150°C and an ash content of 10%. The medium temperature coal tar pitch is Ningxia Qinghua Coal Chemical Group Co., Ltd. medium temperature coal tar pitch, with a softening point of 80°C and an ash content of 8%.
[0045] 70# and 200# asphalt are produced by Shandong Haiyun Asphalt Co., Ltd., SBS-791 is produced by Sinopec, powdered SBR is produced by Shandong Gaoshi Science and Technology Industry and Trade Co., Ltd., L series modified petroleum resin is produced by Shandong Qilong Chemical Co., Ltd., 80 mesh waste tire rubber powder is produced by Hebei Zeyuan Rubber Products Co., Ltd., and mineral powder is produced by Nanyang Jinbo Mining Co., Ltd.
[0046] Comparative Example 1
[0047] 22% of 70# asphalt, 28% of 200# asphalt, 3.5% of styrene-butadiene rubber powder, 2% of thermoplastic styrene-butadiene rubber, 1% of L series modified petroleum resin, 17% of 80-mesh waste tire rubber powder, and 26.5% of talcum powder are used to prepare the self-adhesive coiled material according to the self-adhesive coiled material process.
[0048] Before heat aging, the low temperature flexibility limit temperature of the self-adhesive coil is -33°C; after heat aging, the low temperature flexibility limit temperature of the self-adhesive coil is -23°C; the difference in low temperature flexibility limit temperature before and after is 10°C.
[0049] Before heat aging, the peel strength between the self-adhesive rolls was 1.6 N / mm; after heat aging, the peel strength between the self-adhesive rolls was 1.0 N / mm; the difference in peel strength before and after was 0.6 N / mm.
[0050] Comparative Example 2
[0051] 20% of 70# asphalt, 30% of 200# asphalt, 3% of styrene-butadiene rubber powder, 1.5% of thermoplastic styrene-butadiene rubber, 1.5% of L-series modified petroleum resin, 16% of 80-mesh waste tire rubber powder, and 28% of talcum powder are used to prepare the self-adhesive coiled material according to the self-adhesive coiled material process.
[0052] Before heat aging, the low temperature flexibility limit temperature of the self-adhesive coil is -30°C; after heat aging, the low temperature flexibility limit temperature of the self-adhesive coil is -20°C; the difference in low temperature flexibility limit temperature before and after is 10°C.
[0053] Before heat aging, the peel strength between the self-adhesive rolls was 1.7 N / mm; after heat aging, the peel strength between the self-adhesive rolls was 1.2 N / mm; the difference in peel strength before and after was 0.5 N / mm.
[0054] Example 1
[0055] High-temperature coal tar and medium-temperature coal tar were blended at a mass ratio of 1:3 at 240°C, with a blending speed of 300rpm and a stirring time of 0.5h. After blending, the blended asphalt was obtained, which was the heat-aging-resistant asphalt for self-adhesive polymer-modified asphalt waterproofing membrane. Its softening point was 99°C and its ash content was 8.5%. The blended asphalt was added into the formula of the self-adhesive polymer-modified asphalt waterproofing membrane with SBR as the modifier at an addition amount of 2%:
[0056] 70# asphalt 21.5%; 200# asphalt 27.5%; styrene butadiene rubber powder 3.5%; thermoplastic styrene butadiene rubber 2%; L series modified petroleum resin 1%; 80 mesh waste tire rubber powder 16.5%; talcum powder 26% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 2%.
[0057] The above formula is used to prepare the self-adhesive waterproof membrane process.
[0058] The present invention tests the heat aging resistance, peel strength and low temperature flexibility of the self-adhesive coil according to the above test method:
[0059] Before thermal aging, the low-temperature flexibility limit temperature of the self-adhesive waterproof membrane is -32°C; after thermal aging, the low-temperature flexibility limit temperature of the self-adhesive membrane is -23°C; the difference in low-temperature flexibility limit temperature before and after is 9°C.
[0060] Before heat aging, the peel strength between the self-adhesive waterproof membranes was 1.7N / mm; after heat aging, the peel strength between the self-adhesive membranes was 1.4N / mm; the difference in peel strength before and after was 0.3N / mm.
[0061] Example 2
[0062] High-temperature coal tar and medium-temperature coal tar were blended at a mass ratio of 1:4 at 230°C, with a blending speed of 400rpm and a stirring time of 0.5h. After blending, the blended asphalt was obtained, which was the self-adhesive polymer modified asphalt waterproofing membrane anti-heat aging asphalt, with a softening point of 94°C and an ash content of 8.4%. The blended asphalt was added into the self-adhesive polymer modified asphalt waterproofing membrane formula with SBR as the modifier at an addition amount of 3%:
[0063] 70# asphalt 19.5%; 200# asphalt 29%; styrene butadiene rubber powder 2.9%; thermoplastic styrene butadiene rubber 1.6%; L series modified petroleum resin 1.5%; 80-mesh waste tire rubber powder 15.5%; talcum powder 27% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 3%.
[0064] The self-adhesive waterproof membrane is prepared according to the self-adhesive waterproof membrane process.
[0065] The present invention tests the heat aging resistance, peel strength and low temperature flexibility of the self-adhesive coil according to the above test method:
[0066] Before thermal aging, the low-temperature flexibility limit temperature of the self-adhesive waterproof membrane is -29°C; after thermal aging, the low-temperature flexibility limit temperature of the self-adhesive membrane is -19.5°C; the difference in low-temperature flexibility limit temperature before and after is 9.5°C.
[0067] Before thermal aging, the peel strength between the self-adhesive waterproof membranes was 1.9 N / mm; after thermal aging, the peel strength between the self-adhesive membranes was 1.6 N / mm; the difference in peel strength before and after was 0.3 N / mm.
[0068] Example 3
[0069] High-temperature coal tar and medium-temperature coal tar were blended at a mass ratio of 1:5 at 230°C, with a blending speed of 300rpm and a stirring time of 0.5h. After blending, the blended asphalt was obtained, which was the heat-aging-resistant asphalt for self-adhesive polymer-modified asphalt waterproofing membrane. Its softening point was 92°C and its ash content was 8.3%. The blended asphalt was added into the formula of the self-adhesive polymer-modified asphalt waterproofing membrane with SBR as the modifier at an addition amount of 3.5%:
[0070] 70# asphalt 17%; 200# asphalt 29%; styrene butadiene rubber powder 3%; thermoplastic styrene butadiene rubber 1.5%; L series modified petroleum resin 1%; 80 mesh waste tire rubber powder 18%; talcum powder 27% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 3.5%.
[0071] The self-adhesive waterproof membrane is prepared according to the self-adhesive waterproof membrane process.
[0072] The present invention tests the heat aging resistance, peel strength and low temperature flexibility of the self-adhesive waterproof membrane according to the above test method:
[0073] Before thermal aging, the low-temperature flexibility limit temperature of the self-adhesive waterproof membrane is -27°C; after thermal aging, the low-temperature flexibility limit temperature of the self-adhesive membrane is -17.5°C; the difference in low-temperature flexibility limit temperature before and after is 9.5°C.
[0074] Before heat aging, the peel strength between the self-adhesive waterproof membranes was 1.7N / mm; after heat aging, the peel strength between the self-adhesive membranes was 1.4N / mm; the difference in peel strength before and after was 0.3N / mm.
[0075] As can be seen from the above embodiments, the present invention provides a self-adhesive polymer modified asphalt waterproofing coiled material anti-heat aging asphalt, which is prepared by the following method: high-temperature coal tar and medium-temperature coal tar are blended to obtain self-adhesive polymer modified asphalt waterproofing coiled material anti-heat aging asphalt; the high-temperature coal tar softening point is ≥130°C, and the ash content is ≤15%; the medium-temperature coal tar softening point is 70-85°C, and the ash content is ≤10%; the anti-heat aging asphalt softening point is 95-110°C. The asphalt is blended with high-temperature coal tar and medium-temperature coal tar to obtain a blended asphalt with a softening point of 95-110°C, which is added to a waterproofing coiled material with styrene-butadiene rubber as a modifier, which can improve the heat aging resistance of the self-adhesive asphalt coiled material, and will not produce precipitation caused by the poor compatibility between high-temperature coal tar and petroleum asphalt. The test results show that: the low-temperature flexibility limit temperature difference of the self-adhesive coil before and after heat aging treatment is 9-9.5°C, which is 10°C lower than the low-temperature flexibility limit temperature difference of the self-adhesive coil control group without adding blended asphalt, and the temperature difference before and after aging is reduced by 0.5-1°C; the peel strength difference of the self-adhesive coil before and after heat aging treatment of the embodiment is 0.2-0.3N / mm, which is 0.5-0.6N / mm lower than the peel strength difference of the self-adhesive coil control group without adding blended asphalt, and the peel strength difference before and after aging is reduced by 0.2-0.3N / mm.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A self-adhesive polymer modified asphalt waterproofing membrane anti-heat aging asphalt, prepared by the following method: The high-temperature coal tar and the medium-temperature coal tar are blended to obtain the heat-resistant aging asphalt for the self-adhesive polymer modified asphalt waterproofing membrane; The softening point of the high-temperature coal tar pitch is ≥130°C, and the ash content is ≤15%; the softening point of the medium-temperature coal tar pitch is 70-85°C, and the ash content is ≤10%; the softening point of the anti-heat aging asphalt is 95-110°C.
2. The self-adhesive polymer modified asphalt waterproofing membrane heat-resistant asphalt according to claim 1, characterized in that: The mass ratio of the high-temperature coal tar pitch to the medium-temperature coal tar pitch is (1:2) to (1:6).
3. The self-adhesive polymer modified asphalt waterproofing membrane heat-resistant asphalt according to claim 1, characterized in that: The blending temperature is 230-260°C and the blending time is 30-35 minutes; The blending is carried out under stirring conditions, and the stirring rate is 300-400 rpm.
4. The self-adhesive polymer modified asphalt waterproofing membrane heat-resistant asphalt according to claim 1, characterized in that: The ash content of the heat-aging-resistant asphalt in the self-adhesive polymer modified asphalt waterproofing roll is ≤15%.
5. A self-adhesive polymer modified asphalt waterproofing membrane, the raw materials for preparing the self-adhesive polymer modified asphalt waterproofing membrane comprising the anti-heat aging asphalt described in claim 1.
6. The self-adhesive polymer modified asphalt waterproofing membrane according to claim 5, characterized in that: Self-adhesive polymer modified bitumen waterproofing membrane uses styrene-butadiene rubber as a modifier.
7. The self-adhesive polymer modified asphalt waterproofing membrane according to claim 6, characterized in that: In terms of mass fraction, it includes the following raw materials: 70# asphalt 17-25%; 200# asphalt 27-35%; styrene-butadiene rubber powder 2.8-4%; thermoplastic styrene-butadiene rubber 1.5-2.5%; L-series modified petroleum resin 1-1.5%; 75-85 mesh waste tire rubber powder 15-20%; mineral powder 25-30% and self-adhesive polymer modified asphalt waterproof membrane anti-heat aging asphalt 2-5%.